2019
DOI: 10.1038/s41467-019-12965-1
|View full text |Cite
|
Sign up to set email alerts
|

In situ formation of mononuclear complexes by reaction-induced atomic dispersion of supported noble metal nanoparticles

Abstract: Supported noble metal nanoclusters and single-metal-site catalysts are inclined to aggregate into particles, driven by the high surface-to-volume ratio. Herein, we report a general method to atomically disperse noble metal nanoparticles. The activated carbon supported nanoparticles of Ru, Rh, Pd, Ag, Ir and Pt metals with loading up to 5 wt. % are completely dispersed by reacting with CH3I and CO mixture. The dispersive process of the Rh nanoparticle is investigated in depth as an example. The in-situ detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…Feng et al reported a general strategy to disperse active carbon-supported Rh nanoparticles into single-atom Rh catalyst [ 103 ]. Firstly, active carbon-supported RhCl 3 was thermally treated under nitrogen atmosphere at 300°C for 2 h. The residual was reduced with hydrogen at 300°C for 2 h to obtain the fresh 5 wt% Rh catalyst with Rh nanoparticle size of 4 nm (RhNP/AC).…”
Section: Synthetic Methods For Saecsmentioning
confidence: 99%
“…Feng et al reported a general strategy to disperse active carbon-supported Rh nanoparticles into single-atom Rh catalyst [ 103 ]. Firstly, active carbon-supported RhCl 3 was thermally treated under nitrogen atmosphere at 300°C for 2 h. The residual was reduced with hydrogen at 300°C for 2 h to obtain the fresh 5 wt% Rh catalyst with Rh nanoparticle size of 4 nm (RhNP/AC).…”
Section: Synthetic Methods For Saecsmentioning
confidence: 99%
“…The treatment of sintered Au catalyst with CH 3 I has been shown to be an effective method to restore the activity of an Au/C catalyst for acetylene hydrochlorination reactions [91]. Synergistic effects have been observed in the reactant-induced disintegration of metal nanoparticles [92]. After treating carbon-supported metal nanoparticles (e.g., Ru, Rh, Pd) with a CH 3 I/CO mixture, a volatile M(CO) x I y complex can be produced that can be captured and stabilized by the carbon support, resulting in the redispersion of metal nanoparticles into atomically dispersed species.…”
Section: Trends Trends In In Chemistry Chemistrymentioning
confidence: 99%
“… 28 , 33 38 Atomic dispersion also has the potential to be applied to atomically dispersed materials as well as catalyst regeneration processes, and several examples have appeared. 23 25 , 29 − 31…”
Section: Introductionmentioning
confidence: 99%